Sodium alginate ameliorates health in freshwater fish through gut-liver axis modulation under high carbohydrate diets - Wenlu Zhu; Huilin Zhang; Haitao Pan; Hao Zeng; Wenjun Wang; Yunfeng Liu; Zirui Wang; Qiubai Zhou; Chuanqi Yu (Aquaculture Reports)
High carbohydrate (HC) diets have become a conventional approach in modern aquaculture. However, this feeding strategy frequently compromises the health of high-value economic fish species, which might ultimately impair the farmers’ final profits. Our prior research indicated that Saccharina japonica efficiently reduces harm from HC diets, likely due to its sodium alginate (SA) content. In this study, Monopterus albus were randomly grouped into treatments: a normal diet (20 % carbohydrate, NC), a high carbohydrate diet (32 % carbohydrate, HC), and high carbohydrate diets supplemented with 0.5 % SA (LA). Then our outcomes evinced that LA improves various health-related parameters, including reduction of hepatosomatic index (HSI), serum glucose, triglycerides, and aminotransferase levels, as well as the decrease in hepatic lipid droplets, glycogen, and collagen fiber content. Our transcriptomic analysis on liver tissue showed that detoxification-related differentially expressed genes (DEGs) were less active in HC group than in NC group. In contrast, DEGs linked to fatty acid synthesis increased in LA group versus HC group. A combined analysis of metagenomics and the short-chain fatty acids (SCFAs) profile in the posterior intestinal digesta indicated that LA diets greatly increased concentration of acetic acid. This effect was accompanied by a concurrent reduction in the abundance of the species Marinobacter guineae relative to HC diets. Overall, sodium alginate has demonstrated a substantial enhancement in Monopterus albus’ health by mitigating liver injury and ameliorating intestinal microbiota dysbiosis.